ORAI1 Ca2+ Channel as a Therapeutic Target in Pathological Vascular Remodelling - Shawer, Heba; Norman, Katherine; Cheng, Chew W.; Foster, Richard; Beech, David J.; Bailey, Marc A. (Frontiers in Cell and Developmental Biology, 2021)
In the adult, vascular smooth muscle cells (VSMC) are normally physiologically quiescent cells arranged circumferentially in one or more layers within blood vessel walls. Remodelling of native VSMC to a proliferative state for vascular development, adaptation or repair is driven by platelet-derived growth factor (PDGF). A key effector downstream of PDGF receptors is store-operated calcium entry (SOCE) mediated through the plasma membrane calcium ion channel, ORAI1, which is activated by the endoplasmic reticulum (ER) calcium store sensor, stromal interaction molecules (STIM). This SOCE was shown to play fundamental roles in the pathological remodelling of VSMC. Exciting transgenic linage-tracing studies have revealed that the contribution of the phenotypically-modulated VSMC in atherosclerotic plaque formation is more significant than previously thought, and growing evidence supports the implication of ORAI1 signalling in this pathologic remodelling. ORAI1 also emerged to be an attractive potential therapeutic target as it is accessible to extracellular compound inhibition and the progress of a number of ORAI1 inhibitors towards clinical trials. Here we discuss knowledge of ORAI1-mediated signalling in pathologic vascular remodelling, particularly in the settings of atherosclerotic cardiovascular diseases and neointimal hyperplasia, and the recent developments in our understanding of the mechanisms by which ORAI1 coordinates VSMC phenotypic remodelling, through the activation of key transcription factor, NFAT. In addition, we discuss advances in therapeutic strategies aimed at this ORAI1.